Statebuilding and State-Formation : the Political Sociology of Intervention. - De Guevara, Berit Bliesemann (Routledge studies in intervention and statebuilding., 2012)
This book examines the ways in which long-term processes of state-formation limit the possibilities for short-term political projects of statebuilding. Using process-oriented approaches, the contributing authors explore what happens when conscious efforts at statebuilding 'meet' social contexts, and are transformed into daily routines. In order to explain their findings, they also analyse the temporally and spatially broader structures of world society which shape the possibilities of statebuilding. Statebuilding and State-Formation includes a variety of case studies from post-conflict societi.